2002
DOI: 10.1097/00002030-200203080-00009
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial assessing the impact of phenotypic resistance testing on antiretroviral therapy

Abstract: Antiretroviral treatment guided prospectively by PRT led to the increased use of "active" antiretroviral agents and was associated with a significantly better virological response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
1
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(96 citation statements)
references
References 16 publications
3
87
1
5
Order By: Relevance
“…In some studies among adults, resistance testing was shown to provide short-term benefits, especially after initial HAART failure. [38][39][40] However, a large randomized study showed no benefit of resistance testing. 41 Although resistance testing has been adopted widely, other factors (such as toxicity, tolerability, pill burden, and drug-drug pharmacokinetic and resistance interactions), many of which affect adherence greatly, may be more important than viral resistance results alone in designing salvage regimens involving Ն5 drugs to treat highly resistant virus.…”
Section: E852mentioning
confidence: 99%
“…In some studies among adults, resistance testing was shown to provide short-term benefits, especially after initial HAART failure. [38][39][40] However, a large randomized study showed no benefit of resistance testing. 41 Although resistance testing has been adopted widely, other factors (such as toxicity, tolerability, pill burden, and drug-drug pharmacokinetic and resistance interactions), many of which affect adherence greatly, may be more important than viral resistance results alone in designing salvage regimens involving Ն5 drugs to treat highly resistant virus.…”
Section: E852mentioning
confidence: 99%
“…R esistance testing significantly improves response to antiretroviral therapy in patients infected with HIV type 1 (HIV-1), as was recently demonstrated in retrospective and prospective studies (1)(2)(3). Drug resistance can either be directly assessed by phenotypic assays or can be deduced from genotypic assays, which are based on sequencing of the relevant parts of the viral genome (4).…”
mentioning
confidence: 99%
“…Only randomized prospective trials can provide a conclusive insight into the relative clinical benefit value of interventions based on different systems for predicting HIV-1 drug resistance, as has been demonstrated for sequence-based and phenotypic systems (Baxter et al, 2000;Clevenbergh et al, 2000;Cohen et al, 2002;Durant et al, 1999;Tural et al, 2002). The current results however support further efforts to investigate such clinical benefit of the version 1 LiPA Assay, or any other assay, which measures only a selected number of resistance mutations.…”
Section: Discussionmentioning
confidence: 62%